Forest soil penetration resistance following heavy traffic: A 10‐year field study. (30th June 2021) - Pousse, Noémie; Bonnaud, Pascal; Legout, Arnaud; Darboux, Frédéric; Ranger, Jacques
Abstract: Natural recovery of acidic soils following heavy traffic is assumed to take several decades. The aim of this study was to monitor the recovery of soil penetration resistance (PR) after soil compaction by heavy traffic at two forest sites. The sites, located in northeast France, have soils that differ slightly in pH and silt content. The impact on soil PR following heavy traffic was dependent on the soil water content (WC) at the time of measurement, and, therefore, the entire WC range and corresponding PR values were measured. For the most acidic and silty soil, no difference in PR among treatments was observed when the soils were near saturation; however, the difference in PR values was high when soils were close to wilting point. For the least acidic and silty soil, the impact of heavy traffic on PR could be detected whatever the soil moisture, with the magnitude of the effect dependent on the soil water content and depth considered. Standardized PR values with regard to WC allowed an analysis of the evolution of the effect of heavy traffic with time. Ten years after being subjected to heavy traffic, the PR values in the 0‐ to 40‐cm layer recovered to undisturbed values at the least acidic and silty site, but not WC dynamic. The most acidic and silty soil site did not show any recovery of PR or WC dynamic ten years following traffic, although liming at this site was able to increase the regeneration of PR to undisturbed levels.